Mutual learning of livestock keepers and scientists for adaptation to climate change in pastoral areas - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The purpose of the project is to enhance adaptation to climate variability through effective knowledge sharing processes in vulnerable ecosystems of the arid and semi arid lands (ASALs) of Kenya. This involves development and adaptation of methods that render mutual learning between livestock keepers and scientists more effective.